Correlates of geoxyle diversity in Afrotropical grasslands. (9th January 2022) - Meller, Paulina; Stellmes, Marion; Fidelis, Alessandra; Finckh, Manfred
Abstract: Aim: Tropical old‐growth grasslands are increasingly acknowledged as biodiverse ecosystems, but they are understudied in many aspects. Geoxyle species are a key component in many of these ecosystems, their belowground storage organs and bud banks are functionally diverse and contribute to the grasslands' resilience. However, the drivers of the geoxyles' evolution and (belowground) diversity are little understood. Thus, we combined analyses on the key aspects of diversity, belowground functionality, ancestry, and ecology of geoxyles to provide the first comprehensive understanding of this often overlooked growth form. Location: Southern hemisphere Africa, particularly Angola as a part of the Zambezian phytochorion. Taxon: Geoxyle species. Methods: We assessed belowground bud bank types and biogeographic origins of geoxyles in grass‐dominated vegetation types on the Angolan plateau, covering a broad altitudinal, climatic and geological range. Geoxyles were sampled extensively at three different sites, yielding 118 taxa covering about 59% of the Angolan geoxyle flora. Based on the current distribution of these species in Africa below the equator, we analysed their origins and environmental correlates in a taxonomic, functional and biogeographic context. Results: Geoxyle species numbers and species communities differed strongly among sites, but functional types showed very similar spectra. Geoxyles evolved in multiple lineages and originated in different biomes, and functional types were unevenly associated with lineages and biomes. Furthermore, functional types correlate to specific environmental driver combinations. Main conclusions: Functional diversity is not directly linked to species diversity, but is a result of multiple biogeographic origins that contributed functionally differently preadapted lineages to the Zambezian flora. Thus, geoxyles can occur under different environmental conditions, but require seasonal climates, and open grassy ecosystems subjected to fire, frost and likely herbivory. We highlight the importance of frost as a correlate of geoxyle diversity and emphasize the need for further studies to understand this important and complex growth form.